Hubungan pola asuh orang tua dengan perkembangan sosial anak usia prasekolah - Rizka Fauzia Latif; Indra Tri Astuti; Herry Susanto (JOURNAL OF Community Health Issues, 2026)
Background: Social development was a crucial aspect in forming children's abilities to interact, cooperate, empathize, and adapt to their environment. Parenting styles were one of the main factors that influenced children's social development. Inappropriate parenting styles could impact the weakness of children's social abilities, such as difficulties in communicating, withdrawing, or being unable to follow social rules. Purpose: To identify the parenting styles applied by parents, determine children's social development based on parenting styles, and examine the correlation between parenting styles and preschool children's social development. Method: This study used a cross-sectional design with a sample of 100 preschool children from RA Tarbiyatul Athfal 37 Semarang. Data on parenting styles and children's social development were collected through questionnaires completed by parents. Statistical analysis was conducted using Spearman Correlation test. Results: Showed a significant positive relationship between parenting styles and children's social development (r = 0.653, p = 0.001). Children who received good parenting styles tended to have positive social development, whereas poor parenting styles showed an association with negative social development. Conclusion: There was a strong and significant relationship between parenting styles and children's social development. The implementation of consistent democratic parenting styles, full of affection, and involving open communication was essential to support optimal social development of preschool children.   Keywords: Parenting Styles; Preschool Children; Social Development.   Pendahuluan: Perkembangan sosial merupakan aspek penting dalam pembentukan kemampuan anak untuk berinteraksi, bekerja sama, berempati, serta menyesuaikan diri dengan lingkungan. Pola asuh orang tua menjadi salah satu faktor utama yang memengaruhi perkembangan sosial anak. Pola asuh yang tidak sesuai dapat berdampak pada lemahnya kemampuan sosial anak, seperti kesulitan berkomunikasi, menarik diri, atau kurang mampu mengikuti aturan sosial. Tujuan: Untuk mengidentifikasi pola asuh yang diterapkan orang tua, mengetahui perkembangan sosial anak berdasarkan pola asuh, serta mengetahui keeratan hubungan antara pola asuh orang tua dengan perkembangan sosial anak usia prasekolah. Metode: Penelitian ini menggunakan desain potong lintang (cross-sectional) dengan jumlah sampel 100 anak prasekolah dari RA Tarbiyatul Athfal 37 Semarang. Data mengenai pola asuh dan perkembangan sosial anak dikumpulkan melalui kuesioner yang diisi oleh orang tua. Analisis statistik dilakukan menggunakan uji Korelasi Spearman. Hasil: Menunjukkan adanya hubungan positif yang signifikan antara pola asuh orang tua dan perkembangan sosial anak (r = 0.653, p = 0.001). Anak yang menerima pola asuh kategori baik cenderung memiliki perkembangan sosial yang positif, sedangkan pola asuh kurang menunjukkan keterkaitan dengan perkembangan sosial negatif. Simpulan: Terdapat hubungan yang kuat dan signifikan antara pola asuh orang tua dengan perkembangan sosial anak. Penerapan pola asuh demokratis yang konsisten, penuh kasih sayang, serta melibatkan komunikasi terbuka sangat penting untuk mendukung perkembangan sosial anak prasekolah secara optimal.   Kata Kunci: Anak Prasekolah; Perkembangan Sosial; Pola Asuh.V